Intracellular cytokine detection by flow cytometry in surface marker-defined human peripheral blood mononuclear T cells - Lauer, Fredine T. (Curr Protoc Toxicol, 2017)
In a recent unit in this series, protocols for the isolation, cryopreservation, thawing, and immunophenotyping of HPBMC isolated from peripheral whole blood using cell surface marker (CSM) staining and multi-color flow cytometry analysis were presented. The current procedure describes the detection and quantification of CSM and intracellular markers (ICM), including transcription factors and cytokines, following activation and differentiation of CD4+ T-cells using multi-color flow cytometry. Results indicated that repeatable and robust detection of ICM could be obtained in surface marker-defined T cells that identify functional subsets of cells. There were no observed differences between fresh and cryopreserved HPBMC in eight phenotypes analyzed (T-CD3, Th-CD4, Tmem-CD45RO, activated T-CD3/CD25, Treg- Foxp3/CD25, Th1-IFNγ, Th2- IL-4, Th17-IL-17A). There was an observed difference in activated T- CD3/CD69 in the short term (30–90 days) cryopreserved samples as compared to the freshly isolated samples, which may have resulted from the variance in controls or small sample size.